Genome-Wide Analysis of C2H2 Zinc Finger Gene Family and Exploration of Genes Related to Prickle Development in Zanthoxylum armatum - Nuo Wang; Renhua Huang; Hualin Zou; Yuwei Yi; Jiabao Ye; Weiwei Zhang; Feng Xu; Yongling Liao (Horticulturae)
Zanthoxylum armatum (Z. armatum) is a significant economic tree species known for its medicinal and edible properties. However, the presence of prickles on Z. armatum poses a considerable challenge to the advancement of its industry. Numerous studies have indicated that the C2H2 zinc finger protein (C2H2-ZFPs) families are crucial in the development of plant trichomes or prickles. This study identified 78 ZaC2H2 genes from the Z. armatum genome, categorizing them into three groups and analyzing their protein physicochemical properties, chromosomal locations, conserved domains, and gene structures. The evolutionary analysis indicates that the amplification of ZaC2H2 genes primarily results from whole-genome duplication or segmental duplication, and these genes have undergone strong purifying selection pressure throughout their evolutionary history. The analysis of cis-acting elements revealed that they contain various hormone response elements, such as ABRE, AuxRR, the CGTCA motif, GARE motifs, and TCA elements, which are responsive to ABA, IAA, MeJA, GA, and SA signals. RT-qPCR was employed to assess the expression levels of the candidate genes ZaC2H2-45, ZaC2H2-46, ZaC2H2-49, and ZaC2H2-55 under the treatment of five hormones. The results indicated that the expression levels of the ZaC2H2-46 and ZaC2H2-55 genes were significantly up-regulated under NAA, SA, and MeJA treatments. These results will help to further understand the characteristics of the ZaC2H2 gene family and provide a theoretical basis for studying the development of prickles.